Village Regulations (Perdes): Potentials and Challenges in Realizing Autonomous Village - Februati Trimurni; Bengkel; Munthe, Marhaeni Hardiana (Talenta Publisher, 2021)
This article attempts to analyse the opportunities and challenges of villages in regulating village regulations (Peraturan Desa/Perdes) as a basis for realizing village autonomy and development. Sidoharjo I Pasar Miring is a village in Deli Serdang Regency which routinely has not formulated Perdes in carrying out government affairs, public services, economy and socio-cultural development so that the focus of village development has not been directed along with low legal and political legitimacy regarding programs carried out by the village government. This is a qualitative study using observations, interviews and FGDs as the main data sources. Secondary data consists of both statistical, scientific sources and government documents. The key informants of the study consisted of elements of village government, including the executive, legislative and community leaders. The study found several inhibiting factors for the low effort to enforce Perdes, including those related to competence, integrity, and conflicts of interest as well as technical and political support from local governments as important elements in the Perdes regulatory process. This article recommends the need for capacity building for the formulation elements of Perdes, the involvement of local governments in conducting socialization and monitoring in the formulation of Perdes.